Students’ Perceptions on the Use of Story Maps in Reading Comprehension - Oktaviana, Vira; Aminin, Zainul (JET ADI BUANA, 2021)
In the classroom, students need to have good reading comprehension. Without that, they will not have critical skills for studying academic material. However, many students in Indonesia still have difficulty understanding the text. Using an appropriate strategy can help them understand the text. Story maps can be used can be used for students to help them in understanding the text. This research aims to know students’ perceptions on the use of story maps in reading comprehension, the advantages and the difficulties of using story maps for students’ reading comprehension in class. This research was conducted to the students of tenth grade at one senior high school in Lamongan. The instruments in this study were a questionnaire and interview. The research design of this study used a qualitative research design. The technique to analyze the data were data reduction, data display, and conclusion drawing. The results show that story maps can help the students in understanding the text. Most students felt that they have an improvement in reading comprehension because they felt easy and fast to understand the text. Story maps also help the students understand the structure of the text and it was also an interesting activity. Besides that, the students also faced difficulties when using story maps such as difficult making the story maps, still don’t understand the concept of story maps and difficult to understand the content of the text so they also have difficulty in making story maps.